2007
DOI: 10.1002/jbm.a.31583
|View full text |Cite
|
Sign up to set email alerts
|

Bisphosphonate coating on titanium screws increases mechanical fixation in rat tibia after two weeks

Abstract: Recently published data indicate that immobilized N-bisphosphonate enhances the pullout force and energy uptake of implanted stainless steel screws at 2 weeks in rat tibia. This study compares titanium screws with and without a bisphosphonate coating in the same animal model. The screws were first coated with an approximately 100-nm thick crosslinked fibrinogen film. Pamidronate was subsequently immobilized into this film via EDC/NHS-activated carboxyl groups within the fibrinogen matrix, and finally another N… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
69
0

Year Published

2009
2009
2016
2016

Publication Types

Select...
9
1

Relationship

2
8

Authors

Journals

citations
Cited by 59 publications
(72 citation statements)
references
References 30 publications
3
69
0
Order By: Relevance
“…We found an increase in predicted force at pullout of 8% after 10 days and 32% after 17 days as well as an increase in stiffness of 16% after 10 days and 35% after 17 days for the Zoledronate treated animals. Other studies obtained also similar values two weeks after screw implantation and bisphosphonate release (Tengvall et al, 2004;Wermelin et al, 2008). One more study from the Aspenberg group reported a 41% increase in pullout force for BP coated screws after 4 weeks (Agholme et al, 2011) what corresponds again very well with the 42% increase that we found after the same time period.…”
Section: Discussionsupporting
confidence: 89%
“…We found an increase in predicted force at pullout of 8% after 10 days and 32% after 17 days as well as an increase in stiffness of 16% after 10 days and 35% after 17 days for the Zoledronate treated animals. Other studies obtained also similar values two weeks after screw implantation and bisphosphonate release (Tengvall et al, 2004;Wermelin et al, 2008). One more study from the Aspenberg group reported a 41% increase in pullout force for BP coated screws after 4 weeks (Agholme et al, 2011) what corresponds again very well with the 42% increase that we found after the same time period.…”
Section: Discussionsupporting
confidence: 89%
“…Bisphosphonates represent the largest group of these anti-resorptive drugs currently in clinical use (Rachner et al, 2011). Accordingly, coating of implant surfaces with bisphosphonates has been explored for its ability to improve implant osseointegration and testing in animal studies yielded positive results (Wermelin et al, 2007;Wermelin et al, 2008a). Another approach is to improve osseointegration by stimulation of bone formation.…”
Section: Modified Implants In An Osteoporosis Modelmentioning
confidence: 99%
“…Steel screws were tested for pull-out strength in a computerized materials testing machine (100 R; DDL Inc. Eden Prairie, MN, USA), at a cross-head speed of 0.1 mm/s. These type of measurements have been described in detail earlier [23]. The machine recorded the peak force and the energy uptake until the force had dropped to 90% of maximum.…”
Section: Mechanical Evaluationmentioning
confidence: 99%